2005
DOI: 10.1086/427657
|View full text |Cite
|
Sign up to set email alerts
|

Host Adaptation and Immune Modulation Are Mediated by Homologous Recombination inHelicobacter pylori

Abstract: Rearrangement of genomic DNA via homologous recombination provides an alternative mechanism of gene regulation that is essential for successful colonization of the gastric mucosa by Helicobacter pylori. Inoculation of outbred mice with the H. pylori SS1 wild-type strain elicited a T helper (Th) 2 response and established a persistent infection. In contrast, inoculation with an isogenic H. pylori strain defective for homologous recombination elicited a Th1-mediated immune response and clearance of infection wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…Such genomic plasticity is not advantageous for organisms living in stable environments (40). Nevertheless, genomic plasticity increases microdiversity and enables H. pylori to persist in infections (37,39,41). Similarly, it is likely that the high microdiversity reported for deep-sea vent -Proteobacteria (9) results from the genomic plasticity of -Proteobacteria and confers a competitive advantage enabling this lineage to thrive in ever changing steep physical-chemical gradients.…”
Section: Resultsmentioning
confidence: 99%
“…Such genomic plasticity is not advantageous for organisms living in stable environments (40). Nevertheless, genomic plasticity increases microdiversity and enables H. pylori to persist in infections (37,39,41). Similarly, it is likely that the high microdiversity reported for deep-sea vent -Proteobacteria (9) results from the genomic plasticity of -Proteobacteria and confers a competitive advantage enabling this lineage to thrive in ever changing steep physical-chemical gradients.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental NHPH infections have indeed been shown to evoke a Th2-polarized response (14,16), suggesting that Th2-prone BALB/c mice (27) infected with NHPH can be seen as a critical model for the development of MALT lymphoma induced by NHPH. It has been demonstrated that H. pylori strains mainly stimulate Th1 responses both in humans and in mouse models (28). However, as an exception, the H. pylori strain SS1 does not cause a significant upregulation of gamma interferon (IFN-␥), a signature Th1 marker, in either BALB/c or C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, impaired host colonization of a recombination-deficient Helicobacter pylori mutant strain suggests a functional role for chromosomal rearrangement in H. pylori pathogenesis (29). Like mutator phenotypes, which are observed in some pathogenic species (14,19,20), high-frequency chromosomal rearrangement may provide transient variation for rapid adaptation to a new host environment in host-restricted or niche-adapted strains such as B. pertussis.…”
Section: Discussionmentioning
confidence: 99%